2006
DOI: 10.1242/jcs.03265
|View full text |Cite
|
Sign up to set email alerts
|

p63 is upstream of IKKα in epidermal development

Abstract: The epidermis, the outer layer of the skin composed of keratinocytes, develops following the action of the transcription factor p63. The mouse Trp63 gene contains two promoters, driving the production of distinct proteins, one with an N-terminal trans-activation domain (TAp63) and one without (ΔNp63), although their relative contribution to epidermal development is not clearly established. To identify the relative role of p63 isoforms in relation to IKKα, also known to be essential for epithelial development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 29 publications
(40 reference statements)
5
98
1
Order By: Relevance
“…Further studies are needed to determine if PTPN14 and ING1 are direct transcriptional targets of p63. The functional REs in other target genes recently reported as uniquely regulated by p63 and not p53, such as Shh (Caserta et al, 2006), IKKa (Candi et al, 2006) and PKCg (Ponassi et al, 2006), further support our description of the p63 consensus DNA-binding site and its functional impact on target selectivity in the p53 family.…”
Section: Discussionsupporting
confidence: 87%
“…Further studies are needed to determine if PTPN14 and ING1 are direct transcriptional targets of p63. The functional REs in other target genes recently reported as uniquely regulated by p63 and not p53, such as Shh (Caserta et al, 2006), IKKa (Candi et al, 2006) and PKCg (Ponassi et al, 2006), further support our description of the p63 consensus DNA-binding site and its functional impact on target selectivity in the p53 family.…”
Section: Discussionsupporting
confidence: 87%
“…3E). A recent study, using in vitro experiments, suggested that induction of IKK␣ by ⌬Np63␣ occurs through an indirect mechanism in Saos2 cells (30). However, our in vivo analyses clearly demonstrate that, when commitment to terminal differentiation occurs, ⌬Np63␣ induces Ikk␣ expression by directly interacting with the Ikk␣ promoter.…”
Section: Resultscontrasting
confidence: 45%
“…However, it is known that ΔNp63 isoforms can activate the transcription of target genes through a second transactivation domain (18,34). Furthermore, both TAp63α and ΔNp63 can directly or indirectly control the expression of genes that contribute to epidermal differentiation (20,30,31). In the basal layer of stratified epithelia, either in the epidermis or in the esophagus, the predominant p63 isoform is ΔNp63 (35).…”
Section: Resultsmentioning
confidence: 99%
“…Answering this question is important, because p65RelA and p53/p63 have opposing effects on cell growth in mouse primary fibroblasts: p65RelA promotes cell proliferation and inhibits apoptosis (15)(16)(17), whereas p53/ p63 induces apoptosis or senescence (1,18,19). In stratified epithelia, however, both p63 and p65RelA may work together to control epithelial stratification: p63 has been shown to be an upstream regulator of p65RelA, through its ability to induce IKKα expression (20). Furthermore, Wa3 mice, which spontaneously develop wavy hair, have been reported to carry a mutation in the genomic locus that encodes for the iASPP protein, and it has also been proposed that the observed phenotype is caused by a defect in the NFκB pathway (21).…”
mentioning
confidence: 99%